Pendekatan dalam Mitigasi Bencana Tanah Longsor di Kenagarian Sungai Landia Kecamatan IV Koto Kabupaten Agam - Muhammad Rizky Wahyudi; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to determine the approach to landslide disaster mitigation in Kenagarian Sungai Landia, IV Koto Subdistrict, which is carried out by the Agam District Disaster Management Agency and also by the Sungai Landia village government. This research method is a qualitative method with descriptive type. The research location is in the office of the Regional Disaster Management Agency of Agam Regency and the office of the Wali Nagari Sungai Landia. Data collection using caca interviews, observation, and study documentation. The research informants were several heads of fields, section heads in the Regional Disaster Management Agency of Agam Regency, Wali Nagari Sungai Landia and several staff, several high-ranking officials of the Landia River Kenagarian and the Kenagarian Sungai Landia community. The results showed that mitigation measures had been taken, but the mitigation measures had not been maximally implemented by the Agam District BPBD and the Sungai Landia village government.